2020
DOI: 10.3390/su12020620
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Modeling Analysis of Potential Commute Demand for Carsharing in Shanghai, China

Abstract: Carsharing is an emerging commute mode in China, which may produce social and environmental benefits. This paper aims to develop a commute mode choice model to explore influential factors and quantify their impacts on the potential demand for carsharing in Shanghai. The sample data were obtained from a revealed preference (RP) and stated preference (SP) survey and integrated with level-of-service attributes from road and transit networks. The RP survey collected commuters’ trip information and socioeconomic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…ese time series models may not be applicable to discrete time series variables (e.g., traffic accident count data). To consider both time series and discrete characteristics of the response variables, an integer-valued autoregressive (INAR) Poisson model [30][31][32][33][34] was developed. However, the dynamic characteristics of the influential factors were not adequately described in the INAR model.…”
Section: Introductionmentioning
confidence: 99%
“…ese time series models may not be applicable to discrete time series variables (e.g., traffic accident count data). To consider both time series and discrete characteristics of the response variables, an integer-valued autoregressive (INAR) Poisson model [30][31][32][33][34] was developed. However, the dynamic characteristics of the influential factors were not adequately described in the INAR model.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lack of prior experience of similar services (such as car rental) is likely to deter certain potential customer groups from using carsharing. Both Duan et al (2020), who used a stated preference survey to quantify the impacts of potential carsharing demands in Shanghai, and Zhang and Li (2020), who tested a model based on the theory of planned behavior in a study involving university students in Qingdao, China, reported that individuals who are familiar with car rental programs are more inclined to use carsharing.…”
Section: Key Barriers To Carsharing Demand and Usementioning
confidence: 99%
“…Интересно, что история каршеринга началась в Европе ещё в 1940-х гг. Однако спрос на данный вид услуг значительно вырос в 1990-е гг., и они стали оказываться в странах Северной и Южной Америки, Азии и в Австралии [2]. Несмотря на то, что каршеринг является наиболее распространённой формой совместной мобильности, помимо него существует множество других бизнес-моделей в рассматриваемом сегменте транспортного рынка.…”
Section: модели совместной мобильностиunclassified